How do I hold this thing? Controlling reconstructed Q*berts. (October 2017) - Hodges, James A
Preserving a historically significant video game frequently requires either preserving or adapting a touchable interface for contemporary use. While control techniques are often evaluated in terms of fidelity between in- and out-of-game actions, this essay emphasizes several ways that fidelity must be actively constructed. Bringing a haptic perspective on video gaming into conversation with game history and preservation, this essay examines ways that textual materials surrounding and supplementing a work can be used to construct haptic fidelity. The video game Q*bert is selected as a case study both because of its historical and cultural significance and because it makes idiosyncratic use of controller and force-feedback technologies. The essay concludes that playing Q*bert in a preservation setting requires several unique accommodations at the level of touchable interface, and each accommodation illustrates another way that supplementary texts help construct historical haptic fidelity.